The reaction between 4-aminocytidine and imidate esters - Hayatsu, Hikoya (Nucleic Acids Res, 1978)
4-Aminocytosine reacted rapidly at neutral pH and room temperature with ethylacetimidate to give 3-methyl-5-oxo-5, 6-dihydro- s -triazolo[4,3- c ]pyrimidine. 4-Aminocytidine and 4-aminocytidine 5′-phosphate reacted in the same way. 4-Aminocytosine residues in a copolymer of 4-aminocytidylic acid and cytidylic acid were also convertible to the triazolopyrimidine derivative. Since imidate esters are known to react with proteins, the present finding opened up the possibility of developing a new method for crosslinking between nucleic acid and protein.